Immunohistochemical Expression - Caltabiano, Rosario; Loreto, Carla (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Immunohistochemistry (IHC) is an ancillary method, widely used in pathologists' practice, that allows identifying diagnostic and prognostic/predictive of therapeutic response protein markers on tissue samples by the use of specific monoclonal antibodies and chromogenic substances that guarantee the visualization of an antibody-antigene binding complex under a light microscope [1]. Coon et al., in 1941 [2], first introduced the use of fluorochrome-conjugated antibodies in clinical practice. Since then, IHC has gone from being a useful tool for identifying the differentiation line of otherwise undifferentiated cells to a technique capable of providing not only diagnostic but also prognostic and predictive indications of responses to specific therapeutic options [1,3]. The abovementioned peculiarities have made IHC one of the most used ancillary methods in the histopathological approach to human neoplastic and non-neoplastic diseases [3-5]. This Special Issue contains 11 accepted papers that provide readers with a comprehensive update on current and future applications of IHC in medical practice.